Consequences of Customer Dissatisfaction in Upscale and Budget Hotels: Focusing on Dissatisfied Customers' Attitude Toward a Hotel. Issue 1 (2nd January 2019) - Kim, Bona; Kim, Seongseop (Sam); Heo, Cindy Yoonjoung
ABSTRACT: It is important to understand customer dissatisfaction in order to maintain a sustainable business, given that the negative effects of customer dissatisfaction in service businesses may be even greater than the positive effects of satisfaction. This study investigates customer dissatisfaction and its consequences by focusing on the mediating role of attitude toward a hotel according to different hotel classes related to customer expectation level. The results show a mediating role for attitude in the relationship between customer dissatisfaction and specific negative behavioral intentions. This study broadens our knowledge of customer dissatisfaction and the role of attitude toward a hotel in the relevant literature. The empirical findings demonstrate that regardless of hotel type, customer dissatisfaction significantly affects their attitude and their consequent negative behavioral intention.